Peningkatan Penalaran Matematika melalui Problem Based Learning pada Materi Relasi dan Fungsi - Usman, Agustian; Zakaria, Perry; Pauweni, Khardiyawan A.Y. (Research in the Mathematical and Natural Sciences, 2025)
This study aims to improve students’ mathematical reasoning abilities through the implementation of the Problem Based Learning (PBL) model in the topic of relations and functions. The research employed a classroom action research (CAR) design conducted in a single cycle. The subjects were 28 students from class VIII-6 at SMP Negeri 2 Limboto in the 2022/2023 academic year. Data collection techniques included teacher activity observation sheets, student activity observation sheets, and a mathematical reasoning ability test. The results indicate that the application of the PBL model effectively enhanced students’ mathematical reasoning. This is evidenced by: (1) the average percentage of teacher activity observations reaching 82% in the good category; (2) the average percentage of student activity observations reaching 83% in the good category; and (3) the average score of the mathematical reasoning test reaching 83. These findings suggest that the PBL model is effective in improving students’ reasoning abilities in learning mathematical relations and functions.